A Systematic Literature Review of Digital Skills and Human Resource Readiness for the Industrial Revolution Era 4.0 and 5.0 - Dermawan, Arief; Wening, Nur; Vemberi, Yohannes; Fitriastuti, Lucia Ika (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The Industrial Revolutions 4.0 and 5.0 have significantly transformed the workforce, demanding human resources (HR) to possess digital skills and adaptive readiness. This study aims to identify and analyze the necessary digital skills and HR readiness to address the challenges of these industrial revolutions through a literature review approach. This article analysis of 15 scientific articles published between 2020 and 2025, the research reveals that digital skills such as data literacy, information technology proficiency, and problem-solving abilities are key factors. The readiness of Human Resources (HR) to adopt advanced technologies and human-centric approaches in the Industrial Revolution 4.0 and 5.0 era depends on their willingness to acquire new skills and adapt to rapid transformations. Thus, the success of HR is greatly influenced by organizational readiness and access to technology-based training. The findings of this study provide strategic recommendations for policymakers and practitioners to design effective and relevant HR development programs in the era of Industrial Revolutions 4.0 and 5.0.